2013
DOI: 10.1021/cn4000633
|View full text |Cite
|
Sign up to set email alerts
|

First Experimental Evidence of Dopamine Interactions with Negatively Charged Model Biomembranes

Abstract: Dopamine is essential for receptor-related signal transduction in mammalian central and peripheral nervous systems. Weak interactions between the neurotransmitter and neuronal membranes have been suggested to modulate synaptic transmission; however, binding forces between dopamine and neuronal membranes have not yet been quantitatively described. Herein, for the first time, we have explained the nature of dopamine interactions with model lipid membranes assembled from neutral 1,2-dimyristoyl-snglycero-3-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 66 publications
(233 reference statements)
10
66
0
Order By: Relevance
“…In this respect, we find larger EIC values in the presence of PS than in the presence of PC lipid, which indicates a higher affinity of dopamine for the negatively charged PS lipids, as expected based on electrostatic interactions [13]. However, the orientation to dopamine when bound to membranes is similar for the two lipids since in both cases the EIC values are larger for the Hδ1 and H ε1 sites compared to the Hδ2 site.…”
Section: Discussionsupporting
confidence: 67%
“…In this respect, we find larger EIC values in the presence of PS than in the presence of PC lipid, which indicates a higher affinity of dopamine for the negatively charged PS lipids, as expected based on electrostatic interactions [13]. However, the orientation to dopamine when bound to membranes is similar for the two lipids since in both cases the EIC values are larger for the Hδ1 and H ε1 sites compared to the Hδ2 site.…”
Section: Discussionsupporting
confidence: 67%
“…Similar mechanisms have been previously discussed to explain the interactions between anionic phospholipids, divalent cations and protons [59,60,46,70].…”
Section: Accepted Manuscriptsupporting
confidence: 59%
“…They also estimated the surface pressure changes of the DOPC-DOPE-DOPS monolayers. In addition, using calorimetry tools, Piorecka et al reported the first experimental evidences about the preponderant role of negative charge in the interaction of dopamine with an anionic biomembrane model (DMPC/DMPG) [46], concluding that hydrophobic forces are weaker than electrostatic ones. Furthermore, Drolle et al carried out small-angle neutron scattering and diffraction experiments, together with molecular dynamics simulations, to demonstrate that melatonin (another neurotransmitter) fluidizes DPPC and DOPC bilayers, decreasing their thickness with an increment of the head group area [47].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is due to its robustness and the fact that it is focused on the signals of the ligand, withouta ny need for NMR information on the macromolecular target. [7] In particular,large unilamellar vesicles (LUVs) of 1,2-dimyristoylsn-glycero-3-phosphocholine (DMPC), 1,2-ditetradecanoyl-snglycero-3-phospho-(1'-rac-glycerol) (DMPG), and different mixtures of these two lipids were studied as model membranes by using isothermal titration calorimetry (ITC) and differential scanningc alorimetry.D opamine showedp referentialb inding to PG over PC lipids, with the hydrophobic contributions being ten times weaker than electrostatic forces. However,o nly af ew examples have been reported where membrane mimetics are the macromolecular binding partners.…”
mentioning
confidence: 99%
“…STD NMR spectroscopy relies on the intermolecular fast exchange between as mall molecule and am acromolecular entity,s ot hat the characteristicn egative nuclear Overhauser effect (NOE) of the macromolecule developso n the small ligand.T hus, it is particularly suited for the study of protein-carbohydrate interactions. [7] In particular,large unilamellar vesicles (LUVs) of 1,2-dimyristoylsn-glycero-3-phosphocholine (DMPC), 1,2-ditetradecanoyl-snglycero-3-phospho-(1'-rac-glycerol) (DMPG), and different mixtures of these two lipids were studied as model membranes by using isothermal titration calorimetry (ITC) and differential scanningc alorimetry.D opamine showedp referentialb inding to PG over PC lipids, with the hydrophobic contributions being ten times weaker than electrostatic forces. [6] The first description of the thermodynamics of dopamine interactions with biomembranes was reported af ew years ago.…”
mentioning
confidence: 99%